2013
DOI: 10.1109/tnsre.2013.2255066
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Sensorized Wireless Toy for Measuring Infants' Manual Actions

Abstract: The development of grasping is an important milestone that infants encounter during the first months of life. Novel approaches for measuring infants' manual actions are based on sensorized platform usable in natural settings, such as instrumented wireless toys that could be exploited for diagnosis and rehabilitation purposes. A new sensorized wireless toy has been designed and developed with embedded pressure sensors and audio-visual feedback. The fulfillment of clinical specifications has been proved through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…[ 35 ]. In the study of Serio et al , infants showed a good grade of acceptance to such kind of sensorized toys, as confirmed by the results of preliminary tests that involved nine healthy infants; in particular: (i) the dimensions matched infants’ anthropometrics; (ii) the device was robust and safe; (iii) the acquired signals were in the expected range and (iv) the wireless communication was stable [ 36 ]. Further improvements of these technologies have been performed, within the EU CareToy Project [ 37 ], with a new modular MEMS-based system for intensive, patient specific, home-based and family centred early intervention, managed remotely by rehabilitation staff.…”
Section: Mems-based Sensor Technologies For Human Centred Applicatmentioning
confidence: 94%
“…[ 35 ]. In the study of Serio et al , infants showed a good grade of acceptance to such kind of sensorized toys, as confirmed by the results of preliminary tests that involved nine healthy infants; in particular: (i) the dimensions matched infants’ anthropometrics; (ii) the device was robust and safe; (iii) the acquired signals were in the expected range and (iv) the wireless communication was stable [ 36 ]. Further improvements of these technologies have been performed, within the EU CareToy Project [ 37 ], with a new modular MEMS-based system for intensive, patient specific, home-based and family centred early intervention, managed remotely by rehabilitation staff.…”
Section: Mems-based Sensor Technologies For Human Centred Applicatmentioning
confidence: 94%
“…Cecchi et al [29] incorporated piezoresistive pressure sensors and flexible force sensing resistor (FSR) sensors in sensorised toys to measure infants' reaching and grasping. Serio et al [30] used pressure sensors connected to air chambers to measure the amplitude of the force applied for quantitative monitoring and measuring infants' motor development.…”
Section: Detecting Toy Squeezingmentioning
confidence: 99%
“…Cecchi et al [29] incorporated piezoresistive pressure sensors and flexible Force Sensing Resistors (FSR) sensors in sensorised toys to measure infants' reaching and grasping. Serio et al [30] use pressure sensors connected to air chambers to measure the amplitude of the force applied for quantitative monitoring and measuring infants' motor development.…”
Section: Detecting Toy Squeezingmentioning
confidence: 99%
“…The cubes had a contact area of 72.00 cm 2 , and the balls had a contact area of 64.84 cm 2 between the robot end effector and the force sensor. It was noted that studies on infant grip force within the first 12 months had measured the range to be between 5 to 35 kPa [29,30,39,40,49]. As such, to validate performance in a minimal force application condition, the robot was programmed in position control mode to move 10 mm vertically from z 0 to z 1 with a velocity of 65 mm/s to apply a force F robot = 20 N on the toys.…”
Section: Physical Structurementioning
confidence: 99%